Practical viability of naturally-occurring Ilmenite as a catalyst in advanced oxidation processes - Tichapondwa, Shepherd Masimba (University of Pretoria, 2022)
Dissertation (MSc (Applied Science: Environmental Technology))--University of Pretoria, 2021.